Variasi pH terhadap Kinerja Elektrokoagulasi dan Efisiensi Penyisihan Logam Berat Pb, Cd, dan Ni dari Limbah Artifisial - Agung Nasrullah; Muhrinsyah Fatimura; Reno Fitriyanti (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2026)
Liquid waste containing heavy metals such as lead (Pb), cadmium (Cd), and nickel (Ni) is a serious environmental problem because it is toxic and difficult to degrade naturally. One effective method to overcome this problem is electrocoagulation using aluminum electrodes. The purpose of this study was to determine the effect of pH variations on the removal efficiency of Pb, Cd, and Ni metals using the electrocoagulation method on artificial waste. The study was conducted with pH variations of 3, 5, 7, 9, and 11, with an initial concentration of each metal of 20 mg/L. The parameters analyzed included the final concentration and metal removal efficiency. The results showed that pH significantly affected the performance of electrocoagulation, with optimum efficiency obtained at pH 9. The highest removal efficiency for each metal was Pb at 99.35%, Cd at 97.50%, and Ni at 99.70%. Under these conditions, Al(OH)₃ species are formed, which act as active coagulants in the adsorption and flocculation of heavy metals. These results indicate that the electrocoagulation method is highly effective for treating waste containing heavy metals.Keywords - Aluminum, Electrocoagulation, Heavy Metals, Ph, Removal Efficiency.